Integrated response of crop yields and greenhouse gas emissions to cropland management practices and natural factors: a global meta-analysis - Jiahui Dong; Shikun Sun; Guolong Zhan; Jingxin Sun; Yihe Tang; Yubao Wang (Environmental Research Letters)
The effects of cropland management on yield and greenhouse gas (GHG) emissions vary among crops, and comprehensive and quantitative analyses of relevant factors are needed to make informed management decisions. The study assessed the response of global crop yields and GHG to cropland management and natural factors (including mean annual temperature, mean annual rainfall, soil pH, soil C N ratio (SCN), soil organic matter, crop type, biochar (application rate Brate, biochar feedstock, C N ratio BCN, biochar pH BPH, biochar organic matter BTC), irrigation, N fertilizer (Nrate), tillage, straw management, plastic film mulch, duration of experiment, economic development, geographic location (state, country)) involving 167 papers from 17 crops in 27 countries, with a total of 1249 pairs of observations by using meta-analysis. The results showed that biochar application throughout the year improved crop yields, reduced GHG and was more suitable for use on C _4 crops. The contribution of straw return to CH _4 and CO _2 was 78.3% and 35.6%, respectively. The effect of intermittent irrigation (I-IRR) on the yield of C _4 crop was 25.7% higher than that of C _3 crop. The optimal nitrogen utilization rates for wheat and corn were 253.20 kg·N·hm ^−2 and 239.84 kg·N·hm ^−2 , respectively, and N fertilizer was more effective in reducing GHG of C _3 crops. Among the 20 influencing factors, the relative impact of annual rainfall was the most significant, accounting for 69.3% of N _2 O and 40.39% of CO _2 emissions, respectively. SCN had the most obvious impact on CH _4 、GWP and Greenhouse Gas intensity (GHGI), reaching up to 51.45%、35.98% and 43.46%, This study quantitatively assessed the response of different types of crop yields and GHG emissions to cropland management practices and natural factors, and provided a basis for making management decisions to enhance global crop yields and reduce GHG.